TI_GERICHTE 52.2016.215 vom 21. April 2016 , Commessa pubblica. Attendibilità del prezzo. Divieto di subappalto - TI Tribunale d'appello (2016)
Commessa pubblica. Attendibilità del prezzo. Divieto di subappalto